Dialogue with the Master: Early Shī‘a Encounters with Akbarīan Mysticism - Leila Chamankhah (Teosofi: Jurnal Tasawuf dan Pemikiran Islam, 2020)
Muḥy al-Dīn Ibn ‘Arabī’s theoretical mysticism has been the subject of lively discussion among Iranian Sufis since they first encountered it in the seventh century. ‘Abdul Razzāq Kāshānī was the pioneer and forerunner of the debate, followed by reading and interpreting al-Shaykh al-Akbar’s key texts, particularly Fuṣūṣ al-H{ikam (Bezels of Wisdom) by future generations of Shī‘ī scholars. Along with commentaries and glosses on his works, every element of ibn ‘Arabī’s mysticism, from his theory of the oneness of existence (waḥdat al-wujūd) to his doctrines of nubuwwa, wilāya, and khatm al-wilāya, was accepted by his Shī‘ī peers, incorporated into their context and adjusted to Shī‘a doctrinal platform. This process of internalization and amalgamation was so complete that after seven centuries, it is difficult, if not impossible, to distinguish between Ibn ‘Arabī’s theory of waḥdat al-wujūd, or his doctrines of wilāya and khatm al-wilāya and those of his Shī‘ī readers. To have a clearer picture of the philosophical and mystical activities and interests of Shī‘ī scholars in Iran under Ilkhanids (1256-1353), I examined the intellectual and historical contexts of seventh century Iran. The findings of my research are indicative of the contribution of mystics such as ‘Abdul Razzāq Kāshānī to both the school of Ibn ‘Arabī in general and of S{adr al-Dīn al-Qūnawī in particular on the one hand, and to the correlation between Sufism and Shī‘īsm on the other. What I call the ‘Shī‘ītization of Akbarīan Mysticism’ started with Kāshānī and can be regarded as a new chapter in the history of Iranian Sufism.